Print Literacy Development Uniting Cognitive and Social Practice Theories - Purcell Gates, Victoria (Harvard University Press, 2022)
Is literacy a social and cultural practice, or a set of cognitive skills to be learned and applied? Literacy researchers, who have differed sharply on this question, will welcome this book, which is the first to address the critical divide. The authors lucidly explain how we develop our abilities to read and write and offer a unified theory of literacy development that places cognitive development within a sociocultural context of literacy practices. Drawing on research that reveals connections between literacy as it is practiced outside of school and as it is taught in school, the authors argue that students learn to read and write through the knowledge and skills that they bring with them to the classroom as well as from the ways that literacy is practiced in their own different social communities. The authors argue that until literacy development can be understood in this broader way educators will never be able to develop truly effective literacy instruction for the broad range of sociocultural communities served by schools